2014
DOI: 10.1111/ppl.12291
|View full text |Cite
|
Sign up to set email alerts
|

Global transcriptional profiling of a cold‐tolerant rice variety under moderate cold stress reveals different cold stress response mechanisms

Abstract: Gene expression profiling under severe cold stress (4°C) has been conducted in plants including rice. However, rice seedlings are frequently exposed to milder cold stresses under natural environments. To understand the responses of rice to milder cold stress, a moderately low temperature (8°C) was used for cold treatment prior to genome-wide profiling of gene expression in a cold-tolerant japonica variety, Lijiangxintuanheigu (LTH). A total of 5557 differentially expressed genes (DEGs) were found at four time … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
29
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(30 citation statements)
references
References 63 publications
1
29
0
Order By: Relevance
“…It plays an important role in Asian grain production, which has made a great contribution to food security (Aryal and Kandel 2017;Chauhan et al 2017;Rahaman and Shehab 2019). As a typical subtropical or tropical crop, rice plants are always damaged by cold sress (Zhao et al 2015;Wu et al 2016;Chen et al 2017). This stress is not only detrimental to plant growth and development (Su et al 2010;Thomashow 2010;Kim et al 2017), but also limits spatial distribution and grain productivity (Su et al 2010;Wang et al 2016;Uphoff and Thakur 2019).…”
Section: Introductionmentioning
confidence: 99%
“…It plays an important role in Asian grain production, which has made a great contribution to food security (Aryal and Kandel 2017;Chauhan et al 2017;Rahaman and Shehab 2019). As a typical subtropical or tropical crop, rice plants are always damaged by cold sress (Zhao et al 2015;Wu et al 2016;Chen et al 2017). This stress is not only detrimental to plant growth and development (Su et al 2010;Thomashow 2010;Kim et al 2017), but also limits spatial distribution and grain productivity (Su et al 2010;Wang et al 2016;Uphoff and Thakur 2019).…”
Section: Introductionmentioning
confidence: 99%
“…For example, (Zhang T. et al, 2012) have found more than 500 candidate genes that are significantly up-regulated under low temperatures. Moreover, 183 DEGs related to cold stress have been identified by Chawade et al (2013), 383 DEGs by Yang et al (2015), and more than 2000 DEGs by Zhao et al (2014). Nevertheless, it has been difficult to determine from publicly available transcriptome data which of these candidate genes show consistent expression patterns under stress as well as across a range of cultivars.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, dehydrins, which play a role in the response to cold/drought 44 , had only two members in G. montanum, compared with 38 in P. abies, 28 in P. taeda and 3-15 in angiosperms (Supplementary Table 19). Further analysis of the G. montanum genome also revealed relatively few gene family members of the AP2 domain containing protein families, which are involved in the cold stress response 45,46 , and glutathione peroxidase and glutathione S-transferase families, involved in the oxidant stress response 47,48 . Taken together, these data appear consistent with the hypothesis that the ecological shift to a warm, wet forest habitat is associated with a relaxation of selection pressure on genes associated with water stress and low temperature.…”
mentioning
confidence: 99%